2021
DOI: 10.3390/app11073069
|View full text |Cite
|
Sign up to set email alerts
|

Battery Characterization via Eddy-Current Imaging with Nitrogen-Vacancy Centers in Diamond

Abstract: Sensitive and accurate diagnostic technologies with magnetic sensors are of great importance for identifying and localizing defects of rechargeable solid batteries using noninvasive detection. We demonstrate a microwave-free alternating current (AC) magnetometry method with negatively charged NV centers in diamond based on a cross-relaxation feature between nitrogen-vacancy (NV) centers and individual substitutional nitrogen (P1) centers occurring at 51.2 mT. We apply the technique to non-destructively image s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…NV-ensembles with high NV − concentrations and/or large detection volumes are favored for precision magnetometry [17][18][19][20], for a considerably improved signal-to-noise ratio and sensitivity, which both ideally improve with the square root of the number of sensing spins [21,22]. Therefore, bulk diamonds with NV-ensembles throughout the entire diamond volume are required for many applications such as detecting magnetic nanoparticles [23], battery characterization [24], vector imaging [25,26], and lasing [27,28]. High NV − concentrations require an enhanced nitrogen incorporation in diamonds, especially in the form of isolated-substitutional-nitrogen atoms (called P1 center or N 0 s center) [29,30], which are converted to NV centers via irradiation and annealing.…”
Section: Introductionmentioning
confidence: 99%
“…NV-ensembles with high NV − concentrations and/or large detection volumes are favored for precision magnetometry [17][18][19][20], for a considerably improved signal-to-noise ratio and sensitivity, which both ideally improve with the square root of the number of sensing spins [21,22]. Therefore, bulk diamonds with NV-ensembles throughout the entire diamond volume are required for many applications such as detecting magnetic nanoparticles [23], battery characterization [24], vector imaging [25,26], and lasing [27,28]. High NV − concentrations require an enhanced nitrogen incorporation in diamonds, especially in the form of isolated-substitutional-nitrogen atoms (called P1 center or N 0 s center) [29,30], which are converted to NV centers via irradiation and annealing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that measuring both the amplitude and phase of the magnetic field can be used to reconstruct the eddy currents. This principle finds applications in various areas, such as in the monitoring of fuel cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that measuring both the amplitude and phase of the magnetic field can be used to reconstruct the eddy currents. This principle finds applications in various areas, such as in the monitoring of fuel cells [9,10].…”
Section: Introductionmentioning
confidence: 99%